Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita: Studi Kasus pada Materi Pertidaksamaan Linear Satu Variabel - Nenohai, Eldad Yabes; Riwu, Daniel Lulu; Kaluge, Agapitus Hendrikus (Papanda, 2026)
This study aims to analyze students' mistakes in solving story problems in one-variable linear inequality material. Using a qualitative descriptive method, three grade VIII students of SMP Negeri 1 Kupang were selected as subjects based on the wrong answers in the description test. Data was obtained through written tests and interviews. The results of the study showed errors in understanding the context, estimating and interpreting variables, compiling mathematical models, and performing algebraic procedures. Students also misinterpret the final result so that the answers do not fit the real context. These findings show that students' mastery of algebraic concepts and mathematical modeling abilities is still low. A learning strategy that emphasizes understanding concepts and relating the material to contextual situations is needed to improve students' problem-solving skills.